Biofeedback and cognitive behavioral therapy for Egyptian adolescents suffering from chronic fatigue syndrome - Al-Haggar, Mohammad S.; Al-Naggar, Zienab A.; Abdel-Salam, Mohammad A. (Journal of Pediatric Neurology, 2006)
We aimed to evaluate the efficacy of cognitive behavioral therapy (CBT) aided by biofeedback in rehabilitating Egyptian adolescents who were suffering from chronic fatigue syndrome (CFS). Out of 298 screened individuals with chronic fatigue, only 159 adolescents were eligible for study; of them 63 cases lost follow up and four cases were further excluded because of switch leaving only 92 cases with complete database. Age range of enrolled cases was 10–14 years and male/female ratio (1/2.5). They were recruited from private schools and polyclinics in Eastern province, Saudi Arabia; some cases were referred by psychiatrists in private hospitals of the same area. All cases were diagnosed as CFS according to the recommendations of International CFS Study Group. Patients were randomly allocated to one of two groups; interventional group comprised 50 cases and underwent CBT aided with biofeedback over a period of 18 months applying two protocols according to patient’s activity pattern. Forty-two cases were followed and treated symptomatically and used as control group. Data were processed and analyzed using SPSS version 10.0. The most common symptoms were unrefreshing sleep, headache and myalgia (95.8%, 67.7% and 50% respectively). Patients of interventional group showed marked improvement manifested by decrement of checklist individual strength (decreased 23.1%; 95% confidence interval 19.2–25.4%) and better school attendance (increased 31.5%; 95% confidence interval 29.8–36.6 hours/month) with the disappearance of some self-rated CFS symptoms. CBT aided by biofeedback could be very effective in treatment of adolescents suffering from CFS taking in consideration the stressors and precipitating factors during settings of psychotherapy.
Keywords: Biofeedback; cognitive behavioral therapy; chronic fatigue syndrome; adolescents